2003
DOI: 10.1046/j.1365-2613.2003.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining boundaries during joint cavity formation: going out on a limb

Abstract: Summary. Whilst factors controlling the site at which joints form within the developing limb are recognised, the mechanisms by which articular element separation occurs during the formation of the joint cavity have not been determined. Herein, we review the relationships between early limb patterning, embryonic movement, extracellular matrix composition, local signalling events and the process of joint cavity formation. We speculate that a pivotal event in this process involves the demarcation of signalling bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 80 publications
2
26
0
Order By: Relevance
“…Hyaluronan attenuates synovial fluid loss from flexed joints (Lu et al, 2005) and provides low-load hydrodynamic lubrication (Mabuchi et al, 1994). Also, coupling between HA production and limb movement is crucial for joint cavitation during embryogenesis (Lamb et al, 2003). The present work concentrated exclusively on the coupling between static strain and qḢ A ; further studies are needed to assess the effects of dynamic, cyclical strain and whether it activates additional pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyaluronan attenuates synovial fluid loss from flexed joints (Lu et al, 2005) and provides low-load hydrodynamic lubrication (Mabuchi et al, 1994). Also, coupling between HA production and limb movement is crucial for joint cavitation during embryogenesis (Lamb et al, 2003). The present work concentrated exclusively on the coupling between static strain and qḢ A ; further studies are needed to assess the effects of dynamic, cyclical strain and whether it activates additional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Also HAS trafficking between the plasmalemma and an intracellular pool (Rilla et al, 2005) could be subject to regulation. The Ca 2+ -dependent PKC isoforms (α, β1, β2) can activate c-Raf1, which activates ERK (Kanashiro and Khalil, 1998) leading to the activation of immediate early genes by transcription factors that include activator protein-1, Elk-1 and NF-κB (Hagemann and Blank, 2001), Smad (Lamb et al, 2003), c-fos and fra-1 (Wamel et al, 2000;Chiquet et al, 2003).…”
Section: Upstream: a Role For Ca 2+ Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies in AS cells have shown that mechanically induced ERK activation is both rapid and sustained and that these kinetic characteristics are allied to the formation and maintenance of pericellular matri-ces (8,22). A general mechanism through which ERK activation kinetics may be interpreted has recently been proposed; the immediate early gene product c-Fos has been shown to function as a downstream molecular sensor of ERK signal duration that allows cells to respond appropriately to extracellular signals (23,24).…”
mentioning
confidence: 84%
“…Indeed, disruption in UDPGD in zebrafish (Jekyll mutant) blocks atrioventricular differentiation by modifying the signaling boundaries involved in valve formation (39). The role of UD-PGD-derived HA in boundary formation is also supported by similar cardiac valve disruption in HAS2 (HA synthase 2) knockouts, which is correctable by exogenous HA (40,41).…”
Section: Mechanical Loading Regulates the Phenotype Of Cells At Thementioning
confidence: 99%